Credit Markets with Differences in Abilities : Education, Distribution, and Growth - De Gregorio, Jose.; Kim, Se-Jik. (Washington, D.C. : International Monetary Fund, 1994)
This paper addresses the growth, welfare, and distributional effects of credit markets. We construct a general equilibrium model where human capital is the engine of growth and individuals differ in their education abilities. We argue that the existence of credit markets encourages specialization, by which individuals choose during their youth to work or to receive formal education. This specialization unambiguously increases growth and welfare. The model also shows that in economies with high (low) average level of education abilities, the opening of credit markets induces a more disperse (equal) income distribution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet